2017
DOI: 10.1371/journal.pone.0177792
|View full text |Cite
|
Sign up to set email alerts
|

Identification and expression analysis of starch branching enzymes involved in starch synthesis during the development of chestnut (Castanea mollissima Blume) cotyledons

Abstract: Chinese chestnut (Castanea mollissima Blume) is native to China and distributes widely in arid and semi-arid mountain area with barren soil. As a perennial crop, chestnut is an alternative food source and acts as an important commercial nut tree in China. Starch is the major metabolite in nuts, accounting for 46 ~ 64% of the chestnut dry weight. The accumulation of total starch and amylopectin showed a similar increasing trend during the development of nut. Amylopectin contributed up to 76% of the total starch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…In contrast, the percentages of soluble and reducing sugars decreased in the late Chinese chestnut maturation stage. Zhang et al [5] and Chen et al [6] reported the same trend from 45 to 75 DAF and 60 to 80 DAP in Chinese chestnut, respectively. A similar dynamic pattern was found in wheat with the soluble sugar content decreasing as the grain starch content increased [25].…”
Section: Discussionmentioning
confidence: 69%
“…In contrast, the percentages of soluble and reducing sugars decreased in the late Chinese chestnut maturation stage. Zhang et al [5] and Chen et al [6] reported the same trend from 45 to 75 DAF and 60 to 80 DAP in Chinese chestnut, respectively. A similar dynamic pattern was found in wheat with the soluble sugar content decreasing as the grain starch content increased [25].…”
Section: Discussionmentioning
confidence: 69%
“…Despite the economic and social importance of bananas, there have been relatively fewer studies of bananas compared to other crops, especially in term of fruit development and response to environmental stress . SBE is a key enzyme in amylopectin synthetic pathway that has also been found to be involved in the regulation of seed germination, seedling growth and development, and in response to several abiotic/biotic stresses in many crops (Hamada et al, 2001;Xia et al, 2011;Pei et al, 2015;Chen et al, 2017;Li et al, 2017). In this study, we identified ten MaSBE genes through a genome-wide search of M. acuminata.…”
Section: Discussionmentioning
confidence: 99%
“…The SBE family genes have been reported to associate with the fruit development and ripening process in some plant species, including Malus × domestica (Han et al, 2007), Castanea mollissima (Chen et al, 2017),…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations